Successful Pregnancy in a Patient with Combined Deficiency of Factor V and Factor VIII - Ahmed Ghassan El Adib; Farah Majdi; Mohamed Othmane Dilai; Hamid Asmouki; Ahlam Bassir; Karam Harou; Abderraouf Soumani; Said Younous; Lahoucine Mahmal (Hindawi Limited, 2014)
Inherited combined factor V and factor VIII deficiency (F5F8D) is autosomal recessive transmission disorder. Epistaxis, postsurgical bleeding, and menorrhagia are the most common symptoms. The risk of miscarriage and placental abruption is consequent. We report a case of successful pregnancy in a patient with F5F8D. 20-year-old woman, born of consanguineous parents, third gestate, first parity, two miscarriages, admitted for child birth of a spontaneous pregnancy estimated at 38 weeks and was diagnosed with F5F8D. At admission, patient was hemodynamically stable, with good obstetric conditions. The biologic results showed low levels of PT (52%), factor V (7%), and factor VIII (5%), and the activated partial thromboplastin time was prolonged (68,6%). Parturient was admitted in intensive care unit, maternal and fetal monitoring was performed. Fresh frozen plasma (FFP) and factor VIII concentrates were perfused at the induction of labor. Analgesia used fentanyl titration. The delivery gave birth to a newborn male, with Apgar 10/10 and 3000 g. The puerperium was simple without any important bleeding. Laboratory tests for the newborn were acceptable. Little literature is available on this subject and there are no guidelines available concerning pregnancy; we chose to prescribe a combination of factor VIII concentrate and FFP in pre-, per- and postpartum. The same protocol was successfully used in a patient before dental extraction and prostatectomy. Vaginal delivery is possible, as our case. Management by multidisciplinary team is recommended.